Reseña de: D. Regev (2020): New Light on Canaanite-Phoenician Pottery. Sheffield-Bristol, Equinox Publishing Ltd. - Sáez Romero, Antonio Manuel (SPAL - Revista de Prehistoria y Arqueología, 2020)
Reseña de Regev, Dalit. (2020): New Light on Canaanite-Phoenician Pottery. Worlds of the Ancient Near East and Mediterranean Series, Sheffield, Equinox Publishing Ltd. 223 pp